Growth Response and Yield of Pakchoy Plants (Brassica rapa) On the Wick System of Hydroponic Systems with Various Concentrations of Abmix Fertilizer and Liquid Organic Fertilizer - Bahtiar, Ali; Amalia, Lia; Budiono, Heru (Institute of Computer Science (IOCS), 2021)
The research aims to determine; (1) Effect of interaction between AB Mix Concentration and Liquid Organic Fertilizer on growth and yield components of Pakchoi Plants on axis hydroponic system, and (2) Optimum AB Mix concentration for each administration of POC concentration which gives the best pakchoi yields on axis hydroponic system. The research was conducted in Rancasari Village, Subang Regency, from March to April 2021. The research was carried out with an experimental approach using a factorial randomized block design (RAK) consisting of two factors, namely the first factor was AB Mix fertilizer with three levels (5 ml/l, 10 ml/l and 15 ml/l), and the organic fertilizer factor. three levels of liquid (0 ml/l, 3 ml/l and 6 ml/l) so that in each replication there were 9 treatment combinations and repeated three times. To determine the effect of the treatment of AB Mix fertilizer and liquid organic fertilizer, analysis of variance through the F test was used, with further tests using the Duncan's Multiple Range Test at a significance level of 5 percent. The results showed that: (1) there was an interaction effect between AB mix nutrients and liquid organic fertilizer on plant fresh weight. AB mix fertilizer independently affected plant height, number of leaves per plant, leaf area, chlorophyll index, number of shoots and stomata density. Liquid organic fertilizer independently affects plant height, number of leaves per plant, leaf area, chlorophyll index, number of shoots and stomata density, and (2) AB Mix concentration of 15 ml/l and liquid organic fertilizer 6 ml/l gives plant fresh weight. the highest pakchoy was 388.27 g per plant